1993
DOI: 10.1002/jbm.820270716
|View full text |Cite
|
Sign up to set email alerts
|

Use of polyphosphazenes for skeletal tissue regeneration

Abstract: The hydrolytically unstable polyphosphazenes, poly [(imidazolyl) (methylphenoxy) phosphazenes] and poly [ethyl glycinato) (methylphenoxy) phosphazenes], were studied as potential polymeric supports for cells in tissue regeneration. For bone repair, their specific function would be to support osteoblast growth, forming a bone-polymer matrix. MC3T3-E1 cells (an osteogenic cell line) were seeded onto polymer matrices and cell adhesion and growth as well as polymer degradation were examined. Both imidazolyl- and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 28 publications
2
105
0
Order By: Relevance
“…Conditioned media collected 2 days before each time point (3,7,14, and 28 days) were used. Briefly, the samples were incubated with goat anti-mouse osteocalcin and 125 I mouse osteocalcin followed by donkey anti-goat IgG.…”
Section: Osteocalcin Radioimmunoassaymentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioned media collected 2 days before each time point (3,7,14, and 28 days) were used. Briefly, the samples were incubated with goat anti-mouse osteocalcin and 125 I mouse osteocalcin followed by donkey anti-goat IgG.…”
Section: Osteocalcin Radioimmunoassaymentioning
confidence: 99%
“…A variety of synthetic (e.g., poly-lactic/glycolic acid) or natural polymers (e.g., collagen) have been used as delivery vehicles for cells or growth/morphogenetic factors [e.g., transforming growth factors, bone morphogenetic proteins (BMPs)]. [7][8][9][10] Polymeric scaffolds fabricated using various methods [11][12][13][14] have been used for cartilage repair, 1 nonunion fracture defects, 8,9 oral/maxillofacial defects, [15][16][17][18][19] , and spinal fusion 20,21 as well as nerve 22 and liver 23 tissue repair. Derivatized hyaluronic acid (Hyaff-11) is a new class of a semisynthetic biopolymer that can be fabricated into porous scaffolds for tissue reconstruction and repair.…”
Section: Introductionmentioning
confidence: 99%
“…Also the degradation rates can be modified by varying the nature and ratio of the side groups [11][12][13][14]. Thus, amino acid ester polyphosphazenes have been found to be attractive candidates for biomedical applications [15][16][17]. We have recently demonstrated relatively good mechanical properties, tunable degradation rate, and excellent osteocompatibility of alanine ethyl ester and p-phenylphenoxy cosubstituted polyphosphazenes both in vitro and in vivo [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the fungal growth requires some compounds containing phosphorus and nitrogen atoms (25). The monophosphazene molecules contain phosphorus and nitrogen atoms and therefore they have a positive effect on the growth yeast cells for both S. cerevisiae and C. albicans Ibim et al (27) and Laurencin et al (28) indicated that polyphosphazenes have positive effects on cells and tissue cultures and are required for cell growth and tissue regeneration. Also, Veromese et al (29) found that antibacterial or anti-inflammatory drugs, useful in periodontal tissue regeneration, could be entrapped in the phosphazene membranes and realized both in vitro and in vivo at such a rate that ensured therapeutic concentrations in the surroundings tissue.…”
Section: Discussionmentioning
confidence: 99%